Electrical machines, drives, and power systems - Wildi, Theodore (Prentice Hall, 2002)
For one-semester, undergraduate-level courses in Motor Controls, Electric Machines, Power Electronics, and Electric Power. This best-selling text employs a theoretical, practical, multidisciplinary approach to provide introductory students with a broad understanding of modern electric power. The scope of the book reflects the rapid changes that have occurred in power technology over the past few years--allowing the entrance of power electronics into every facet of industrial drives, and expanding the field to open more career opportunities.